Mutual funds for dummies - Tyson, Eric (Eric Kevin) (--For dummies., 2016)
Newly revised and updated, Mutual Funds For Dummies, 7th Edition provides readers with insight on how to find the best-managed funds that match their financial goals. With straightforward advice and a plethora of specific and up-to-date fund recommendations, Eric Tyson helps readers avoid fund-investing pitfalls and maximize their chances of success.